FACTORS IN DEVELOPING A CULTURE OF GENDER EQUALITY IN THE PROCESS OF STUDENTS’ ADAPTATION TO THE EDUCATIONAL ENVIRONMENT IN SPECIALIZED SCHOOLS - Gulomov, Nozimjon Kozimjonovich (SCIENCE and SOCIETY, 2026)
This article analyzes the importance of fostering a culture of gender equality in the process of students’ socio-psychological adaptation to the educational environment of specialized schools. It provides a scientific and practical account of how gender stereotypes present in educational institutions affect students’ level of adaptation. The study examines the gender neutrality of the school environment, the views of teachers and parents, as well as the role of trainings and initiatives as research objects. Based on an analysis of international and local experiences, specific recommendations are developed to promote equality in the educational environment. The article substantiates the need to create a fair and psychologically healthy environment free from gender stereotypes.